FACTORS ASSOCIATED WITH UTILIZATION OF ANTENATAL CARE SERVICES IN THE UPTD PUSKESMAS AREA OF GUNUNG SITOLI SELATAN DISTRICT - Zai, Niat Triwati (TOUR HEALTH JOURNAL, 2024)
Background: ANC visits aim to monitor the welfare of the mother and child at least four times during pregnancy. In 2016, K1 and K4 coverage in Gunung Sitoli City, namely K1 was 4.4% and K4 was 89.6%. The amount of coverage has decreased compared to 2017 where K1 was 95.3% and K4 was 95.3%. The impact of pregnant women who do not receive ANC at least 4 times will not be found in premature labor, high risk pregnancies, nor will abnormalities be found which will increase the death rate and pain during pregnancy. The low level of utilization of health services for pregnant women at Community Health Centers is caused by many factors. Several factors influence the use of ANC, namely, predisposing factors including (age, education, employment, parity, and pregnancy spacing), and supporting factors including family income and demand factors (health of pregnant women). Purpose: To determine the factors associated with the utilization of antenatal care services in the UPTD Puskesmas area of Gunung Sitoli Selatan Subdistrict. Method: The type of research used in this research is quantitative with a cross sectional design. The population in this study were all pregnant women who underwent ANC examinations in June-July 2023 in the UPTD area of ​​the South Gunungsitoli District Health Center for the 2023 period, totaling 74 respondents, all of whom were used as the sample (Total Sampling). Data collection uses Primary and Secondary Data using questionnaire sheets and observation sheets. Data analysis used the chi-square test via cross tabulation with α<0.05. Results: There is no relationship between maternal employment and utilization of ANC services with a Chi Square value of P = 0.429. There is a relationship between knowledge and utilization of ANC services with a Chi Square value of P = 0.000. There is a relationship between attitude and the use of ANC services with a Chi Square value of P = 0.000. There is a relationship between family support and service utilization with a Chi Square value of P = 0.000. Conclusion: There is a relationship between knowledge, attitudes and family support with the use of ANC services in the UPTD area of ​​the Gunung Sitoli Selatan sub-district health center. Disscusion and Conclusion: Suggestion: it is hoped that the UPTD Coordinating Midwife at the Gunungsitoli Community Health Center will plan health promotions to pregnant women regarding the use of ANC services by involving various local sectors